Report of Cladorhiza bathycrinoides Koltun (Demospongiae) from North America and a new species of Farrea (Hexactinellida) among sponges from Cordell Bank, California - Reiswig, Henry M. (Zootaxa, 2020)
A small collection of five Sponges made by E/V Nautilus on Cordell Bank National Marine Sanctuary, California, include the first report of the crinorhyzid Cladorhiza bathycrinoides Koltun off North America and a new species of Hexactinellida, Farrea. cordelli n. sp. The other three sponges in the collection are known to occur off the surrounding North-East Pacific coast, but new geographic or depth distributions are reported for these.